1980
DOI: 10.1128/iai.27.1.133-139.1980
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated immunity against herpes simplex induction of cytotoxic T lymphocytes

Abstract: The conditions required for the induction of both primary cytotoxic T lymphocytes (CTL) in vivo and secondary CTL in vitro against herpes simplex virus type 1 (HSV-1)-infected cells were defined. Primary CTL responses occurred only in mice exposed to infectious HSV-1. These responses, which were shown to be mediated by T lymphocytes, peaked at 1 week and had disappeared by 2 weeks after infection. The level of primary cytotoxicity was enhanced by treatment of mice with cyclophosphamide before infection. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 35 publications
1
79
0
Order By: Relevance
“…The importance of glycoproteins to the host immune response elicited against a herpesvirus infection has been well documented (15,25,27,42). The glycoprotein gD of HSV-1 has been shown to be a type-common antigen capable of inducing a host immune response which can protect against both HSV-1 and HSV-2 (10).…”
Section: B) Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of glycoproteins to the host immune response elicited against a herpesvirus infection has been well documented (15,25,27,42). The glycoprotein gD of HSV-1 has been shown to be a type-common antigen capable of inducing a host immune response which can protect against both HSV-1 and HSV-2 (10).…”
Section: B) Discussionmentioning
confidence: 99%
“…The envelope of herpes simplex virus type 1 (HSV-1) contains at least four antigenically distinct glycoproteins, designated gB, gC, gD, and gE (2,20,37). Glycoproteins gB, gC, and gD appear to be the principal immunogens involved in inducing both the humoral and cellular host immune responses (16,25,27,42).…”
mentioning
confidence: 99%
“…Moreover, limited HSV-1 replication is superior to exposure of the immune system to purified viral proteins (Chan et al 1989, McDermott et al 1989, Fitzgerald-Bocarsly et al 1991. Indeed, immediate early gene expression is sufficient to induce a natural killer cell-mediated immunity (Fitzgerald-Bocarsly et al 1991), while ultraviolet light or heat inactivation of virus reduces the ability to form HSV-specific cytotoxic T lymphocytes (Lawman et al 1980). Likewise, infection of experimental animals with viral mutants that have an aborted replication cycle protects them from the development of encephalitis and keratitis (Nguyen et al 1992, Morrison & Knipe 1994.…”
Section: Hsv-1mentioning
confidence: 99%
“…Although most viral polypeptides elicit an antibody response, it is generally thought that the viral surface glycoproteins represent the (immunologically) most important of the viral antigens [reviewed by Crumpacker, 19801. Supporting this view the glycoproteins of HSV have been shown to represent the major target antigens for such diverse immune functions as virus neutralization [Powell et al, 1974;Cohen et al, 1978;Eberle and Courtney, 1980;Para et al, 19821, antibody-dependent cellular cytotoxicity [Norrild et al, 1979, 19801, natural kdler cells [Bishop et al, 19831, and cytotoxic T lymphocytes [Lawman et al, 1980;Carter et al, 19811. In recent studies where the relative titers of antibodies directed against individual viral polypeptides were examined, it was found that antibody titers to the gB glycoprotein were consistently high in immune sera relative to titers of antibody directed against other viral proteins [Eberle and Mou, 19831. However, very high titers of antibody reactive with a series of unidentified low molecular weight viral proteins (ranging from 34,000 to 49,000 daltons molecular weight) were also commonly found in human immune sera.…”
Section: Introductionmentioning
confidence: 99%